PROFIT EQUALIZATION RESERVE AND DSN MUI NO: 127/DSN-MUI/VII/2019 IN MAQASHID SYARIAH PERSPECTIVE - Safitri, Nurfala; Maftukhatusolikhah, Maftukhatusolikhah (Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aims to analyze the application of Profit Equalization Reserve (PER)and its relationship with the DSN MUI fatwa NO: 127 / DSN-MUI / VII / 2019 in the view of maqasid sharia.PER is used to maintain the competitiveness of yields in Islamic banking. The reserve fund can be used when the sharing of financing results goes down. That way, depositors' interest is maintained, because the reduced profit sharing can be covered with reserve funds. Based on existing sources, the authors argue that PER can be applied in the Islamic economic financial system as long as it does not violate existing regulations. However, the application of PER is not only applied to Islamic banking but also applies to the sukuk wakalah bil al istithmar.This is evidenced by the existence of the term PER which is allowed in DSN MUI NO: 127 / DSN-MUI / VII / 2019 concerning Sukuk wakalah bi al-Istithmar. The reason for the inclusion of PER in DSN MUI NO: 127 / DSN-MUI / VII / 2019 is because the result of the consideration of the meaning of Wakalah bi al-Istithmar is the wakalah contract to invest and develop Muwakkil's assets either in return (Wakalah bi al-Ujrah) or without compensation(Wakalah bi ghairi al-Ujrah).